PRODUCT INNOVATION, A SURVIVAL STRATEGY FOR SMALL AND MEDIUM ENTERPRISES IN NIGERIA - O. S. Ibidunni; Oluwole Iyiola; Ayodotun S. Ibidunni (European Scientific Journal, ESJ, 2014)
The study investigated how product innovation, as a strategy, enhances the survival of the small and medium enterprises in Nigeria, using Prodco Foods Nigeria Limited as a study. Among the objectives set out were the relationship between product innovation and the survival of Small and Medium Enterpries (SMEs), changes in tastes and preference of consumers necessitating product innovation, and whether product innovation increases sales volume of SMEs. The research study was developed around the product innovative and dynamic capability innovative theories. The theoretical model of the product life-cycle was used in developing the three hypotheses that were tested at 0.05 significant levels; through the survey of one hundred and forty respondents. Copies of the questionnaire were administered to the respondents sampled. The validity and reliability of the instrument were measured at Cronbach’s alpha of 0.63 and alternative form validity of 0.59. The findings revealed that there is a significant relationship between product innovation and the survival of SMEs, also, that changes in tastes and preference of consumers necessitate product innovation, and that product innovation increases sales volume of SMEs. The conclusion from the research findings showed that there is need for SMEs to carry out research on product innovation; in other to meet and fulfill the demand and expectations of all consumers and the market. It was recommended that adequate finance, condusive environment, and public policy framework should be developed by the Nigerian governments to support and encourage the SMEs.